Using Digital Newspaper as Creative Learning Media to Boost Students’ Higher Thinking Skills - Helda Jolanda Pentury; Anastasia Dewi Anggraeni (Deiksis, 2021)
Through creative pedagogical application currently, the concepts of pedagogical strategy which are more technologically oriented than they used to be, transform education into a way where creative and innovative students’ perspectives and motivation are nurtured. Digital Newspaper concept of alignment, which expresses from social science and humanity has been developed useful in creating innovative and skillful academic environments, as it apply to integrate learning with cognitive, kinesthetic, technological, and social-culture aspects learning form.  The research conducted by observing students' projects and reveals the way they identify, classify, analyze and create creative learning from the topics of Jakarta Post online content as a learning media. The result of this study shows that using this media which has various current materials can increase students’ higher thinking critically, creatively and innovatively in English language learning. We recommend that in future research, researchers use more online newspaper which is more engaging with the real-world and give positive impact to boost students’ high order thinking skills to solve the problem, to analyze, and to make decisions in their English language performances. Keywords: Creative Media, Language Skills, Thinking Skills